The process of activated sludge ozonation effect of ozone on cells, flocs, macromolecules and nutrient release - Meng, Xianrong (Water science and technology : a journal of the International Association on Water Pollution Research, 2015)
The purpose of this research is to investigate the activated sludge ozonation process. Results revealed that bacteria destruction and cell solubilization were not obvious when ozone dose was lower than 11 mgO₃/gMLSS (MLSS: mixed liquor suspended solids), while pores appeared on the sludge and bacterial disappeared from floc surface. In the range of 11-90 mgO₃/gMLSS, ozone had significant effect on cell permeabilization and disruption. Meanwhile, a large quantity of macromolecules and nutrients were released from bacteria cells. Additionally, efficiency of ozone utilization was low but specific solubilization related to cell lysis was high at this level. Greater than 90 mgO₃/gMLSS, the number of live cells and dead cells were both stable, and the quantity of material in bulk liquid increased slowly. The specific solubilization ratio decreased while the efficiency of ozone utilization began to increase. This indicated that ozone oxidized the macromolecules in the bulk liquid instead of bacteria cells at high ozone dose